2018
DOI: 10.1590/1983-21252018v31n226rc
|View full text |Cite
|
Sign up to set email alerts
|

PROBIOTIC POTENTIAL OF Bacillus cereus AGAINST Vibrio spp. IN POST-LARVAE SHRIMPS

Abstract: -Bacillus spp. have been used against diseases caused by bacteria that affect cultured shrimp, providing beneficial effects on the host shrimps by altering their microbial community, and improving zootechnical indexes. The objective of this work was to evaluate the effects of a diet supplemented with Bacillus cereus-a bacterium with probiotic potential-on post-larvae Litopenaeus vannamei shrimps grown in laboratory. The experiment lasted for fifteen days and consisted of six treatments-control (T 1 ), probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…These isolate probably synthesis different anti-Vibrio compounds which give different effects on shrimp survival rate, as well as indicating a high diversity of anti-Vibrio compounds produced by these sponge-associated bacteria. Supporting this result, the shrimp fed with probiotics Bacillus cereus exhibited a higher survival rate (51.48 ± 16.51%) compared to untreated shrimps (53.01 ± 8.48%), as reported by Vidal et al (2018). Another study also reported that spongeassociated bacteria could enhance shrimps survival rate ranging 70-90%, higher than the positive control which is only inoculated with V. harveyi (38.3±2.9%) (Rini et al 2017).…”
Section: Discussionsupporting
confidence: 75%
“…These isolate probably synthesis different anti-Vibrio compounds which give different effects on shrimp survival rate, as well as indicating a high diversity of anti-Vibrio compounds produced by these sponge-associated bacteria. Supporting this result, the shrimp fed with probiotics Bacillus cereus exhibited a higher survival rate (51.48 ± 16.51%) compared to untreated shrimps (53.01 ± 8.48%), as reported by Vidal et al (2018). Another study also reported that spongeassociated bacteria could enhance shrimps survival rate ranging 70-90%, higher than the positive control which is only inoculated with V. harveyi (38.3±2.9%) (Rini et al 2017).…”
Section: Discussionsupporting
confidence: 75%
“…Vibrio alginolyticus was also reported to possess probiotic effects against Aeromonas salmonicida (Hoseinifar et al, 2018 ). The use of Bacillus cereus isolated from the intestine of shrimps Litopenaeus vannamei is an example of successful re-colonization of the host intestine at the post-larval stage, probably due to competitive exclusion via the secretion of antimicrobial substances, especially resulting in effective suppression of V. parahaemolyticus and V. harveyi , justifying Bacillus cereus use as probiotic bacterium in shrimp larviculture (Vidal et al, 2018 ). This is an example of probiotic screening from natural host microbiomes that can be successfully applied across several aquaculture systems.…”
Section: Microbial-based Strategies To Prevent Vibrio ...mentioning
confidence: 99%
“…Their use in aquaculture systems such as the BFT and aquamimicry also improves the zootechnical process of the system (De Melo et al, 2015). Probiotics are living microorganisms that are added to the aquaculture environment through food or water to exert beneficial effects on the host health and its growth performance by modulating the guts' microflora (Balcázar et al, 2006;Merrifield et al, 2010;Dawood et al, 2016Dawood et al, , 2018Vidal et al, 2018). The use of probiotics in aquaculture is a suitable alternative to therapeutics for controlling occurrences of infectious diseases and they can contribute to improve water quality (Liu et al, 2010;Jahangiri and Esteban, 2018;Biswas et al, 2019;Nathanailides et al, 2021).…”
Section: The Application Of Probiotics In Aquamimicry Systemmentioning
confidence: 99%
“…Specific probiotics, including B. subtilis, produce essential vitamins such as vitamin B1 and vitamin B12 (Ghosh et al, 2007). Therefore, these probiotics are increasingly used to enhance growth, resistance to pathogenic microbes in farmed shrimp, improve nutritional efficiency and feed conversion ratio, and reduce production costs (Vidal et al, 2018). In general, the addition of probiotics to the aquamimicry system has the following functions:…”
Section: The Application Of Probiotics In Aquamimicry Systemmentioning
confidence: 99%